Exploring Finnish university students' perceived level of critical thinking - Orszag, Aaron (2015)
Critical thinking is believed to be a 21 st century skill that many employers consider crucial when hiring recent graduates. However, it is debated whether critical thinking should be taught in academic foreign language courses at the tertiary level, which primarily aim to develop students’ language and communication skills. This localized, exploratory research examines Finnish university students’ self-reported critical thinking skills and dispositions after completing the compulsory academic English courses. The aim of the research is to examine what skills and dispositions students feel competent in, and discover if there is a correlation between students’ self-reported critical thinking ability and such factors as gender, age, years spent in university, and the importance attributed to critical thinking. The second aim is to understand how students view critical thinking and to identify activities that contributed to their critical thinking development. A mixed-methods questionnaire was used to collect data, which was developed on the basis of Facione’s (2013) framework of critical thinking, consisting of six skills and seven dispositions. Twenty-four students participated in the study, including students from various faculties, such as education, humanities, business, information technology, and sports and health sciences. The data was collected at a university in Central Finland in the fall of 2014, and was analyzed using nonparametric statistical methods. The results indicate that the participants are quite confident in their critical thinking ability but have a rather narrow view of the skills and dispositions that constitute critical thinking. The students also perceived reading and social interaction as important factors contributing to their critical thinking development. The findings suggest that an infusion method, which focuses on field-specific subject matters and uses activities that explicitly focus on various components of critical thinking, can increase students’ awareness of critical thinking skills and dispositions. The results also indicate that using dialogic teaching methods and strategies, which utilize the power of meaningful talk, can contribute to the development of students’ critical thinking ability.